1962
DOI: 10.1111/j.1440-169x.1962.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Respiration of Sea-Urchin Spermatozoa

Abstract: It has been reported that the tricarboxylic acid cycle intermediates have little or no effect on O2 uptake of spermatozoa of several sea-urchin species (SPIKES 1949, MOHRI 1957 a), except Arbaciu punctulata spermatozoa of which are said to show increased O2 uptake in the presence of succinate, a-ketoglutarate and glutamate (BARRON and GOLDINGER 1941 a, b). Since, however, the presence of enzymes essential for the tricarboxylic acid cycle, succinic and malic dehydrogenase and fumarase, in sea-urchin spermatozoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The sea urchin spermatozoon consists of a head, a midpiece, and tail. The sperm head of D. setosum contains mainly nucleus, similar to those of other species of sea urchin (Afzelius and Mohri, 1966; tions reported by Mohri (1957). The failure to utilize phospholipids appears to be due to the low activity of phospholipase A, in D. setosum spermatozoa (Table 4).…”
Section: Previous Studies Have Shown That the Lipids In Dmentioning
confidence: 74%
See 1 more Smart Citation
“…The sea urchin spermatozoon consists of a head, a midpiece, and tail. The sperm head of D. setosum contains mainly nucleus, similar to those of other species of sea urchin (Afzelius and Mohri, 1966; tions reported by Mohri (1957). The failure to utilize phospholipids appears to be due to the low activity of phospholipase A, in D. setosum spermatozoa (Table 4).…”
Section: Previous Studies Have Shown That the Lipids In Dmentioning
confidence: 74%
“…Diadema setosum belongs to the order Diadematoida, which are primitive types of sea urchins in comparison with the orders Echinoida and Arbacioida (Shigei, 1974). Previous studies have shown that the phospholipid content of D. setosum spermatozoa decreases following incubation in seawater (Mohri, 1957). However, the D. setosum spermatozoa contain TG, as do the sea urchin spermatozoa of the order Arbacioida (Mita et al, 1994b).…”
Section: Wiley-liss Incmentioning
confidence: 96%
“…pH 7.0-7.5) is used as a mechanism to reduce sperm respiration in the 12 gonad and seminal fluid with the internal pH (pHi) of sperm being pH ca. 6.8 (Chia and Bickell, 1983;Mita and Nakamura, 2001;Mohri and Yasumasu, 1963). The inhibitory effect of low pH on sperm motility is over ridden in nature by the respiratory dilution effect of seawater (increased oxygen tension) and by the egg jelly peptides that promote sperm motility at low pH (Brokaw, 1990;Chia and Bickell, 1983;Darszon et al, 2008;Ward et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Since CO 2 inhibits both respiration and motility of the spermatozoa, 127) it is plausible that release from the high P CO 2 in the testis or in dry sperm by dilution with seawater causes an increase in intracellular pH (pH i ) which in turn activates dynein ATPase activity. 128) In fact, a temporary decrease in the content of ATP as well as that of phosphagen has been observed immediately after dilution.…”
Section: Initiation and Activation Of Movementmentioning
confidence: 99%